The Experiences of Mid-career and Seasoned Orchestral Musicians in the UK During the First COVID-19 Lockdown - Cohen, Susanna; Ginsborg, Jane (Frontiers in Psychology, 2021)
The introduction of social distancing, as part of efforts to try and curb the spread of the COVID-19 pandemic, has brought about drastic disruption to the world of the performing arts. In the UK the majority of professional orchestral musicians are freelance and therefore self-employed. These players, previously engaged in enjoyable, busy, successful, portfolio careers, are currently unable to earn a living carrying out their everyday work of performing music, and their future working lives are surrounded by great uncertainty. The aim of the present study was to examine how established professional musicians are experiencing this period, and to look for similarities and differences between the experiences of musicians in the middle of their performing careers (aged 35 – 45), with those of older players (aged 53 and over). Single semi-structured interviews were carried out over Zoom with 24 freelance, self-employed orchestral musicians; 12 mid-career musicians aged 35 – 45, and 12 seasoned musicians aged 53 and over. Thematic analysis identified themes common to both groups: the loss of a much-loved performing career, missing music making and colleagues, and anxiety about the future of the music profession. It also identified differences between the two groups: challenges to their identity as a musician, the extent of their anxiety about finances, the extent of their emotional distress, attitudes towards practising and engaging in collaborative music making, and confusion over future career plans. Findings are discussed with reference to lifespan models of musicians’ career development and the PERMA model of wellbeing.